2014
DOI: 10.1016/j.diamond.2014.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Principles for designing sputtering-based strategies for high-rate synthesis of dense and hard hydrogenated amorphous carbon thin films

Abstract: Principles for designing sputtering-based strategies for high-rate synthesis of dense and hard hydrogenated amorphous carbon thin films, Diamond and related materials, 2014. 44, pp.117-122. http AbstractIn the present study we contribute to the understanding that is required for designing sputtering-based routes for high rate synthesis of hard and dense hydrogenated amorphous carbon (a-C:H) films. We compile and implement a strategy for synthesis of a-C:H thin films that entails coupling a hydrocarbon gas (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…22 The presence of C 2 H 2 introduced additional interactions of plasma electrons leading to dissociation and ionization of C 2 H 2 along with the interactions of plasma electrons with the buffer gas and sputtered C. This process facilitated an increased amount of deposited C (tenfold increased deposition rates), and the resulting films exhibited hardness higher than 25 GPa and mass densities in the order of 2.32 g/cm 3 . The promising prospect of the resulting DLC:H films was their low H content which did not exceed 10 at.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 The presence of C 2 H 2 introduced additional interactions of plasma electrons leading to dissociation and ionization of C 2 H 2 along with the interactions of plasma electrons with the buffer gas and sputtered C. This process facilitated an increased amount of deposited C (tenfold increased deposition rates), and the resulting films exhibited hardness higher than 25 GPa and mass densities in the order of 2.32 g/cm 3 . The promising prospect of the resulting DLC:H films was their low H content which did not exceed 10 at.…”
Section: Introductionmentioning
confidence: 99%
“…In order to elucidate the effect of admixing Ne in Ar and Ar/C 2 H 2 atmosphere, we also compare the resulting film properties with our previous studies. 21,22 The plasma properties are investigated by measuring electron energy distribution functions (EEDF) (thereby determining electron temperature and electron density from EEDF), which, contrary to our expectations, shows that higher electron temperatures are obtained when the process gas (Ne þ Ar) contains C 2 H 2 . The plasma properties are also investigated by studying the behavior of the discharge current under different gas phase composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, Aijaz et al [23] demonstrated that hydrogenated amorphous carbon thin film can be synthesized with low hydrogen quantity in Ar/ C 2 H 2 discharge. They argued that the high plasma density of superimposed HiPIMS and dcMS facilitates to reduce the hydrogen quantity in the deposited film through chemical sputtering of growing film surface, and thereby hardness and mass density of the film are increased.…”
Section: State Of the Art Of A-cn X Materialsmentioning
confidence: 99%
“…The mechanical and tribological properties of carbonbased coatings can be tailored by controlling the energy and flux of the depositing ions, radicals and molecules to substrates [17,18] in various high plasma density discharge-based deposition processes such as cathodic vacuum arc (CVA) [19], pulsed laser deposition (PLD) [20], inductively coupled plasma (ICP) [21], plasma-enhanced chemical vapor deposition (PECVD) coupled with electron cyclotron resonance [22], and magnetron sputtering [23]. Comparing to direct current magnetron sputtering (dcMS) and radio frequency magnetron sputtering (RFMS), highpower impulse magnetron sputtering (HiPIMS) process is known to generate higher plasma density (10 19 m -3 comparing to 10 17 m -3 in dcMS) [24,25].…”
Section: State Of the Art Of A-cn X Materialsmentioning
confidence: 99%